Oposición a los principios para el ejercicio de los derechos constitucionales y los requisitos para ocupar un puesto en el servicio público - Espinosa González, Ana Yessenia (2016)
The thesis on titled "OPPOSITION OF PRINCIPLES FOR THE EXERCISE OF RIGHTS AND CONSTITUTIONAL REQUIREMENTS TO OCCUPY A PLACE IN THE PUBLIC SERVICE" explains one way criticizes the violation of constitutional rights and principles that are fundamental to people and their rights. The Constitution of the Republic of Ecuador existing Article 11 establishes that he exercise of rights shall be governed by several principles, among which we highlight the following " All people are equal and enjoy the same rights, duties and opportunities. No one shall be discriminated against on grounds of ethnicity, place of birth, age , sex , gender identity , cultural identity , marital status, language, religion, ideology , political affiliation, criminal record , socio- economic status, immigration status , sexual orientation, health, carry HIV , disability, physical difference , or any other distinction , personal or collective , temporary or permanent , which has the purpose or effect of impairing or nullifying the recognition , enjoyment or exercise of rights. The law shall punish any discrimination. The State shall take affirmative action to promote real equality in favor of the right holders are in a situation of inequality." More in Article 10 of the Organic Law of the Public Service , provides special prohibitions on the performance of a position, function , or dignity in the public 5 sector and which reads "Persons against whom issued final conviction for the crimes they had of : embezzlement, bribery, extortion , illicit enrichment, and generally those who have been convicted of frauds against state institutions are forbidden to perform in any form of a position, function or dignity in the public service "and as paragraphs 1 and 2 of Article 3 of the Regulations to the Organic Law of the Public Service where he has to present a certificate stating that the applicant has not been convicted of embezzlement, bribery, extortion , illicit enrichment, and generally those they have been convicted of frauds against state institutions . The application of these requirements by those responsible for public institutions are causing injury to the Ecuadorian citizenship by the fact that it is not fair that a person is discriminated against and prevented from entering the Public Service for the commission of crimes of bribery, embezzlement , graft , malfeasance , bribery, illicit enrichment, and in general, for fraud and mismanagement of public funds and assets , and not have been convicted by customs offenses , trafficking in narcotic drugs or psychotropic substances , money laundering , sexual harassment, sexual exploitation, trafficking, smuggling or violation , which clearly attentive to one of the principles for the financial year in which it states that no person shall be discriminated against her criminal record . For this situation it is important and desirable inquiry Legal Member of this problem in order to arrive at effective measures to address it.